Allogeneic hematopoietic stem cell transplantation for T‐prolymphocytic leukemia: a report from the French society for stem cell transplantation (SFGM‐TC). (13th September 2014) - Guillaume, Thierry; Beguin, Yves; Tabrizi, Reza; Nguyen, Stéphanie; Blaise, Didier; Deconinck, Eric; Redjoul, Rabah; Cornillon, Jérôme; Guillerm, Gaëlle; Contentin, Nathalie; Sirvent, Anne; Turlure, Pascal; et al.
Abstract T‐prolymphocytic leukemia (T‐PLL), a rare aggressive mature T‐cell disorder, remains frequently resistant to conventional chemotherapy. Studies have suggested that allogeneic hematopoietic stem cell transplantation (HSCT) might possibly serve to consolidate the response to initial chemotherapy. The current report summarizes the outcome of 27 T‐PLL cases identified in the registry in French Society for stem cell transplantation (SFGM‐TC). Prior to HSCT, 14 patients were in complete remission (CR), 10 in partial response, three refractory, or in progression. Following HSCT, 21 patients achieved CR as best response. With a median follow‐up for surviving patients of 33 (range, 6–103) months, 10 patients are still alive in continuous CR. Overall survival and progression‐free survival estimates at 3 yr were 36% (95% CI: 17–54%) and 26% (95% CI: 14–45%), respectively. The relapse incidence after HSCT was 47% occurring at a median of 11.7 (range, 2–24) months. Overall cumulative incidence of transplant‐related mortality was 31% at 3 yr. These results suggest that HSCT may allow long‐term survival in patients with T‐PLL following induction treatment; however, it is associated with a significant rate of toxicity.